Estudos hidrossedimentológicos e de qualidade de água no Rio Piquiri - Angst, Fernando (2009)
The objective of this paper was to evaluate the hidrossedimentologic parameters, evaluate the hidrologic dates of the ANA (National Agency of the Waters) and the parameters physic-chemical of the water of the station Bridge of Piquiri, and relating them to the systems of the soil use of the basin. They were monitored the parameters of the flood, concentration of suspention sediments and the water quality parameters, total nitrogen, nitrite, nitrate, phosphorus, pH, turbidity and electrical condutivicty, during the period of August of 2007 to April of 2008 in the station Bridge of Piquiri, town of Ubiratã, BR-369. They determined the rating curve of flood (R2=0,99), concentration of suspension sediment (R2=0,95), total day discharge of sediments (R2=0,98) and turbidity in function of suspension sediments (R2=0,94), being that all presented good settlements. The results indicated that can be classified in a very decrease it moderated the output of sediments of the basin. It analyzes of the river discharge established by the ANA showed variations of flood when compared to the values of the present study. The analysis of the suspention sediments concentration of the ANA data series showed a settlement very under its correlation. The physical analysis indicated a good quality of water of the basin, therefore the parameters did not surpass the limits established by the Resolution CONAMA no 357/05. It is able to conclude that the basin finds-itself in satisfactory environmental conditions and that the conservation approaches of use of soil employees in the basin contribute for the maintenance of the quality of the water.